2022
DOI: 10.1590/1519-6984.261032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trichoderma harzianum and Bacillus thuringiensis with reducing rates of NPK on growth, physiology, and fruit quality of Citrus aurantifolia

Abstract: Continuous use of chemical fertilizers gradually shrinks the crop yield and quality, and these adverse effects can be reduced by adopting new sustainable practices such as the use of manure, biofertilizers, and nano fertilizers. Limited information is existed on the application of Trichoderma harzianum and Bacillus thuringiensis microbes to improve lemon seedlings growth, physiology, and fruit formation. Therefore, the current study is aimed to evaluate the effects of T. harzianum and B. thuringiensis microbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Plant canopy (crown) is also influenced by height, and plant branching, the higher the plant and plant branching will be directly proportional to the width of the plant crown in chili [15]. The application of T. harzianum and B. thuringiensis can increase the number of leaves and crowns of Patchouli leaves compared to the control treatment [16], increasing plant size because the application of Trichoderma sp. can increase the C-organic content in the soil and ultimately improve crop quality [17].…”
Section: Resultsmentioning
confidence: 99%
“…Plant canopy (crown) is also influenced by height, and plant branching, the higher the plant and plant branching will be directly proportional to the width of the plant crown in chili [15]. The application of T. harzianum and B. thuringiensis can increase the number of leaves and crowns of Patchouli leaves compared to the control treatment [16], increasing plant size because the application of Trichoderma sp. can increase the C-organic content in the soil and ultimately improve crop quality [17].…”
Section: Resultsmentioning
confidence: 99%
“…2.5 t BSF also increased maize stem diameter by 9% and 18% in S1 and S2 respectively. Studies have shown that application of Trichoderma led to an increase in stem diameter by 23%, 42% and 27.3% respectively [25,69,70).…”
Section: Effects Of Land Preparation Methods and Organic Amendment On...mentioning
confidence: 99%
“…The maximum Increase in fruit weight following use of Trichoderma asperelloides might be due to its effect in cell division and cell elongation. Trichoderma asperelloides is also reported to promote growth by increasing plasticity of cell wall followed by hydrolysis of starch into sugar which reduces cell wall potential, resulting in the entry of water into the cell and causing its elongation Abdelmoaty et al [15]…”
Section: Fresh Weight Of Fruit (G)mentioning
confidence: 99%